Hubungan Pencemaran Karbon Monoksida dalam Rumah dengan Kejadian ISPA di Desa Sungai Alat Kabupaten Banjar - Imam Santoso; Darmiah Darmiah (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2015)
Abstract: Relationship of Carbon Monoxide Pollution in House With The Upper Respiratory Tract infection In Desa Sungai Alat Kabupaten Banjar. The data showed 64.2 % of households in South Kalimantan residents use charcoal and firewood for cooking, so the room in a house filled with smoke. In addition to the state of the smoke could also come from outside , because the habits of the people who set fire to dry land in the dry season. This phenomenon is predicted to be potential risk of respiratory tract infections. This study aims to determine the relationship of carbon monoxide pollution in homes with the upper respiratory tract infection in Desa Sungai Alat Kabupaten Banjar. Using cross sectional study design. The number of samples taken 28 infants in total population. Analysis used logistic regression. The results of the research data showed levels of CO in the average house of 0.42 mg / m3 in the range of 0.19 to 1.62 mg / m3 . The number of infants who suffer from respiratory 42.9 %. Houses that use firewood as much as 53.6 % , and home to the unhealthy category as much as 78.6 % . Temperatures in the average home 32.6 0C , and air humidity in the average home 71.41 %. Bivariate analysis using logistic regression, there was no significant association between levels of CO with the upper respiratory tract infection in infants ; similarly no significant association between the control variables with the dependent variable. To do a home assessment form should be conducted validity assessment. In further studies the expected number of samples propagated to the toddler . Keywords: pollution , carbon monoxide , upper respiratory tract infection